Chromogranin a gene variants influence survival at old age through pleiotropic effects on multiple age-related traits - Crocco, Paolina; La Grotta, Rossella; De Rango, Francesco; Passarino, Giuseppe; Dato, Serena; Rose, Giuseppina (Frontiers in Aging, 2025)
Aging, age-related diseases, and longevity are interconnected processes influenced by shared molecular and genetic mechanisms. In this study, we investigated the role of genetic variation in the Chromogranin A (CHGA) gene, which encodes a multifunctional precursor of regulatory peptides, in human longevity and age-related traits. Using a case-control design with two age cohorts (older adults: 65–85 years; long-lived: 86–107 years), we analysed nine selected CHGA single nucleotide polymorphisms (SNPs) for associations with survival to advanced age and relevant clinical parameters. Five SNPs (rs9658628, rs9658631, rs9658634, rs7159323, and rs7610) were significantly associated with longevity (FDR q < 0.05). In the older adult cohort, the 5′-UTR rs9658628-A allele was associated to reduced odds of reaching advanced age and correlated with increased insulin resistance (TyG index), type 2 diabetes, and lower cognitive performance (MMSE scores), traits typically linked to higher mortality risk. Paradoxically, this allele was also associated with a lower risk of cardiovascular disease, suggesting pleiotropic effects potentially mediated by its regulatory effects on CHGA expression across different tissues. Functional annotation supported rs9658628 as an expression quantitative trait locus (eQTL) for CHGA and neighboring genes (ITPK1, FBLN5 genes in particular) in relevant tissues. Additionally, the 3′-UTR rs7610-T allele was associated with both increased diastolic blood pressure and enhanced survival, highlighting the complexity of blood pressure regulation in aging. Although statistical significance for clinical trait associations was lost after FDR correction, these findings suggest that genetic variations in CHGA exert a complex and multifactorial influence on pathways related to metabolism, cognition, and vascular health, with possible consequences for longevity. This intricate pattern could be due to the multiple, sometimes opposing, functions of CHGA and its active fragments. The biological rationale and potential clinical implications of these associations call for further investigation and independent confirmation.